Apareamiento y sexualidad humana (2010)
ABSTRACT: The author of "Human Mating and Sexuality," recalls the idea of psychoanalysis, where the notion of subject is different from individual. Subject inhabited by language and from this minimal definition is possible to verify the importance to the human subjectivity of one's body image, trainers - the image and body - of being and having. This distinction helps to understand that sex is not the functioning of certain organs, but, in the opinion of the author, "of what it means for everybody to be a man or a woman." Sex is the result of a law -which prohibits-, the desire -at fault- and the pulsion -which is satisfied. Erotic love and life of contemporary men and women are illustrated with these assumptions and concepts.